Change in mineral nutrients contents of five ridge gourd (Luffa acutangula (L.) Roxb.) varieties affected by root-knot nematode (Bangladesh Journal of Botany, 2019)
Mineral nutrient changes in 5 Ridge gourd varieties inoculated with root-knot nematode, Meloidogyne incognita were investigated. Five ridge gourd varieties, namely Priya, BSS-1009, Aneeta, Aarti and Harsha were inoculated with root-knot nematode and studied their effects on the changes of mineral nutrients contents of shoots and roots. The contents of Ca, Mg, Fe, Zn, Cu and Mn varied greatly among the varieties in both shoot and root. Some changes in mineral nutrients were observed due to the inoculation of root-knot nematode. The percentage of Ca, Mg, Fe, Zn, Cu and Mn were found lower in inoculated shoot and root samples than the healthy counterpart in most cases. The lowest Ca content was found in Priya in both shoot and root but Mg content was minimum in Aarti variety.